BEAUTY AND FASHION TRENDS - Axmedova Sevara; Adilova Muslima (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Fashion and beauty are often touted to be synonymous with women but men are equally interested in these. Lately, it is found that men also follow the style and like to live a fashionable life. Beauty for them is personal grooming that enhances their overall persona. The Fashion & Beauty section holds articles on emerging fashion and beauty trends that people like to follow these days.